Investigating the efficacy of a moving bed biofilm reactor for the removal of the antiretrovirals tenofovir, emtricitabine, nevirapine, ritonavir and efavirenz from synthetic wastewater - Mokgope, Herman D. (Vaal University of Technology, 2022)
South Africa utilises more antiretroviral (ARV) compounds per capita than any other nation in the fight against Human Immune Deficiency Virus (HIV) or acquired immunodeficiency syndrome (AIDS). Considering the main entrance pathways of antiviral drugs into the urban water cycle, excretions via urine or faeces from treated individuals play a dominant role. Due to the limited efficiency of conventional biological treatment (activated sludge), ARVs were detected in South African wastewater treatment plant effluents and surface waters. This poses a threat to aquatic environments due to the toxicity of ARVs and can be a potential contributor to ARV resistance due to persistent low level ARV exposure in the general population. This study investigated the efficacy of a moving bed biofilm reactor (MBBR) for ctybtri8nthe elimination of five ARV compounds i.e., tenofovir, emtricitabine, nevirapine, ritonavir and efavirenz from synthetic wastewater. Furthermore, the study also looked at the shift in microbial community compositions of biofilms in the MBBR due to exposure to the ARV compounds. Lastly, the ecotoxicity of the MBBR’s influent and effluent along with the actual ARV compounds were examined. The capacity of ARV degradation by the MBBR was investigated by spiking synthetic wastewater influent with 10 μg/L of five ARV compounds. Actual removal during treatment was assessed by sampling the inlets and outlets of the reactor. A targeted solid phase extraction method with Ultra High Pressure Liquid Chromatography coupled to quadrupole time of flight mass spectrometry (LC-MS/MS) was used to quantify the five ARV compounds. Microbial diversity (alpha-diversity) of seeded sludge from a full-scale municipal WWTP and biofilm samples from a laboratory scale MBBR system during pre- and post-introduction of ARV compounds was investigated by Illumina sequencing of the 16S rRNA gene. Ecological toxicity of the MBBR’s influent and effluent along with the five ARV compounds was determined using the Vibrio fischeri, Daphnia magna and Selenastrum capricornutum toxicity test kits and measured as EC50. After MBBR treatment; Nevirapine, Tenofovir, Efavirenz, Ritonavir and Emtricitabine all showed marked reduction in concentration between the influent and effluent of the MBBR. On average, the percentage removed for Nevirapine, Tenofovir, Efavirenz, Ritonavir and Emtricitabine was 62.31%, 74.18%, 93.62%, 94.18% and 94.87% respectively. Microbial diversity results demonstrated that the introduction of antiretroviral drugs affects the bacterial community composition and diversity considerably. For instance, Nitrosomonas, Nitrospira and Alicycliphilus were found to be higher in post introduction of ARV compounds biofilm samples than in biofilm samples before the introduction of ARV compounds. The EC50 for Tenofovir, Emtricitabine, Nevirapine, Ritonavir and Efavirenz were 82.5, 41.7, 39.3, 60.3 and 0.21 mg/L respectively for S. capricornutum; 81.3, 50.7, 49, 87.1 and 0.43 mg/L respectively for D. magna; and 73.5, 55.1, 41.3, 83.6 and 0.55 mg/L respectively for V. fischeri. The EC50 of the influent and effluent were found to be above 100% concentration, therefore they could not be specifically determined. The ecotoxicity results show that ARV compounds are potentially toxic to the environment, with efavirenz being more toxic than the other four ARV compounds tested. Since there were no toxic effects observed from the effluent, it can be assumed that mineralisation has occurred, or the transformation products are of less or equal toxicity to the influent (because the influent did not show any toxic effects to the model organisms tested).
Ph. D. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Antiretroviral compounds; Polluted water; Biological treatment; Wastewater treatment; Moving bed biofilm reactor (MBBR); Tenofovir; Emtricitabine; Nevirapine; Ritonavir; Efavirenz; Synthetic wastewater; Dissertations, Academic -- South Africa.; Water -- Pollution -- South Africa.; Waste products.; Sewage -- Purification -- Biological treatment.